Seasonal Variation in Physico-Chemical Parameters of Palar River in and Around Vaniyambadi Segment, Vellore District, Tamil Nadu, India - Prabhahar, C (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT In the present investigation the physico-chemical characteristics in Palar River water at Vaniyambadi segment was analysed to assess the water quality. The physico-chemical parameters like Temperature, pH, Electrical conductivity (EC), Total hardness (TH), Total alkalinity (TH), Chlorides (Cl), Dissolved oxygen (DO), Biological oxygen demand (BOD), Chemical Oxygen demand (COD) Turbidity, Total solids (TS), Total dissolved solids (TDS), Total suspended solids (TSS), Phosphates (PO4) , Nitrates (NO3) and Sulphates (SO4) were considered. The overall analysis, it was observed that the fluctuations in the Physico-chemical parameters of water samples. The Palar River daily has been facing the problems of municipal sewage, industrial wastes and anthropogenic activities.